Measuring low-rate gas flows of boreholes in coal mines by the needle increasing flow rate method. Issue 5 (September 2019) - Wang, Kai; Wang, Liang; Zhang, Xiang; Lou, Zhou; Xin, Chengpeng; Du, Feng
A novel method named the needle increasing flow rate method (NIFRM) is proposed to measure the excessively low gas flow rates of extraction boreholes in coal mines. The main idea of the NIFRM is that when the flow rate of a branch extraction pipe of the borehole is lower than the minimum measurable flow rate of the gas extraction analyzer, a needle can be inserted into the branch extraction pipe to allow some air from the roadway to rush into the branch extraction pipe to increase the flow rate temporarily; then the gas parameters are measured and calculated successfully. To verify the rationality of this method and further optimize its parameters, the software FLUENT is applied to conduct a numerical simulation. The numerical simulation results show that the methane concentration will reach a satisfying equilibrium quickly after the air is introduced into the branch extraction pipe. The range and standard deviation of the methane concentration at 1.0 m downstream of the needle are 0.05% and 0.01%, respectively. The pressure difference between the inlet and outlet of the model is less than 10 Pa, indicating that almost all of the negative pressure of the gas extraction in the main extraction pipe is transmitted to the deep part of the branch extraction pipe. From the numerical simulation results, it is safe to say that the negative effect of the increasing flow rate is completely negligible by inserting the needle in the gas extraction system. Lastly, the NIFRM was applied to study the influence of coal seam permeability anisotropy on gas extraction in a coal mine, and the method was further verified.